Avaliação da aptidão da madeira de seis clones de híbridos de eucalyptus para o processamento mecânico - Silva, Luciana Ferreira da (2018)
The objective of this work was to evaluate the wood characteristics of six Eucalyptus hybrid clones of 14 years old in order to select those with the best dendrometric characteristics, chemical, physical and mechanical properties and biological resistance suitable for the production of sawn wood. The characteristics of 18 trees (three of each clone), such as taper, relation heartwood: sapwood, pith eccentricity, and grain diversion were evaluated. The evolutions of the base cracks and top of logs shortly after cutting the trees were determined. The physical properties (basic density and dimensional stability of the wood), mechanical properties (parallel compression to fibers, static flexion and Janka hardness), chemical characteristics (holocellulose, lignin, total extractives and ash) and the biological resistance of wood (accelerated decay (brown and white rot) and xylophagous (underground and dry wood) termites] were evaluated. The effect of the treatments was verified by applying the analysis of variance and F test (p < 0.05) and, when significant, the Scott Knott test (p < 0.05) was applied to discriminate the means. For tree density, clone C, followed by E, produced denser wood, and A, B and F of lower densities. There was no difference between the cracks developed at the base of the logs of the evaluated clones. At the top of clones C, D and E, the highest crack index occurred, and the lowest at A, B and F. When evaluating the wood in a wet and dry state, clone A cracked less. For the evaluated conditions 100 days were sufficient for the wood to enter in equilibrium with the environment. In general, for wood density, clone C presented values higher than the others and A produced wood of lower density and greater dimensional stability. For the mechanical tests, the clones C and F were the most resistant. The position in the wood that had the highest content of extractives and lignin was the external core. The highest amount of ash and holocellulose was observed in the inner core. The clone C was generally the most resistant to xylophagous organisms.